Transformation of Interactive Based Pancasila Education Learning and Student Culture - Mujiwati, Yuniar; Romadhon, Romadhon; Sofinadya, Diba; Muthomimah, Muthomimah (Actual Insight : Lembaga Penelitian Pengembangan, Penerbitan dan Publikasi, 2025)
This research aims to improve the quality of learning in Pancasila and Citizenship Education to be more participatory, adaptive, and contextual through the integration of interactive approaches based on the needs of students and responsive to the local cultural background. The background of this research is based on the findings that the learning process is still dominated by conventional lecture methods that do not actively involve students, thus having an impact on low motivation, participation, and learning outcomes. The subjects of the study were 31 students of class VIII-E State Junior High School 17 Malang with heterogeneous characteristics in terms of academic and socio-cultural abilities. The research method used is Class Action Research with the Kemmis and McTaggart spiral models which are carried out in two cycles, each consisting of the stages of planning, action implementation, observation, and reflection. Data was collected through observation, interviews, learning outcome tests, and documentation, then analyzed qualitatively and quantitatively. The results of the study showed a significant increase in student motivation, participation, and learning outcomes. Learning completeness increased from 45.2% in the pre-cycle to 74.2% in the first cycle, and reached 87.1% in the second cycle. The average score of students also increased from 69 to 82. Contextual interactive activity-based interventions tailored to the needs and cultural realities of learners have proven to be effective in creating a fun, relevant, and meaningful learning atmosphere. These findings contribute to the development of differentiation and local context-based Pancasila and Citizenship Education learning models in secondary schools.